COMPARATIVE STUDY OF SPRING BOOT AND PLAY FRAMEWORK FOR PAYMENT WEB APPLICATIONS - Pavan Kumar Joshi, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Due to the growing popularity of e-commerce and other digital forms of payment systems, there is a paramount requirement for web application frameworks that can offer high levels of security while at the same time exhibiting scalability. When it comes to the frameworks for web development using Java there are a countless number of them. However, the two most prominent and rich in features are Spring Boot and Play Framework. This research work proceeds with a proper comparison of the two frameworks in detail with special emphasis on the use of these frameworks in building payment web applications since the targeted frameworks are well suited for this type of application since performance, scalability, security, and speed of development are critical success factors in building payment web applications. Through this process of analyzing these frameworks according to these criteria, such as general and specific performance abilities with different loads, scalability, intrinsic and added security measures, the complexity of development with the frameworks and the availability of support from the community, respectively, the goal of the study is to break the comparisons down to give a wholesome understanding of each of the frameworks. This analysis is based on the main experiments of payment applications, which aim to reflect real-life processes, so the author reveals practical results to demonstrate how each of the frameworks works in practice. Thus, the findings revealed the promising features of Spring Boot and some of the challenges of its utilization for the creation of payment applications to provide developers and organizations with a comprehensive guide to choosing the most suitable framework for each specific application. Finally, this research work will help to fill the gap in knowledge and practice in relation to the construction of payment web applications that offer necessary performance, reliability, and security.